Pengenalan Konsep Pra Matematika pada Anak Usia Dini melalui Permainan Tradisional Genggong - Lili Nofriyanti; Nur Hazizah (Jurnal Halaqah, 2020)
This research is a literature study that aims to find a picture of the stimulation of the ability to recognize pre-mathematical concepts of children through traditional genggong games. The method used in this research is a descriptive qualitative research method with a literature study. In the study of this literature, study researchers used various written sources such as articles, journals, and documents that are relevant to the research. The results of the review of several traditional genggong study journals can improve the ability of children to recognize pre-mathematical concepts of children. In the study of literature studies, it was concluded that the Traditional Genggong Game can improve the ability to recognize children's pre-mathematical concepts in the learning process.